220k views
5 votes
Show work and explain with formulas.

23. Find the sum of the geometric series: 1/9 + 1/3 + 1 + ... + 2187

24. In a geometric sequence, the first term is 27 and the common ratio is 1/3. Find the sum of the first 6 terms.

25. The sum of the first n terms of the geometric sequence is -6, -12, -24, ... is -762. Find the value of n.​

User Niesha
by
4.7k points

2 Answers

3 votes

23 Answer: \bold{\dfrac{29,524}{9}}

9

29,524

Explanation:

\begin{lgathered}\dfrac{1}{9}+\dfrac{1}{3}+1+...+2187\\\\\\a_1=\dfrac{1}{9}=3^{-2}\qquad r=3\qquad a_n=2187\\\\\underline{\text{Find n:}}\\a_n=a_1\cdot r^{n-1}\\2187=3^{-2}(3)^{n-1}\\2187=3^{n-3}\\3^7=3^{n-3}\\7=n-3\\10=n\end{lgathered}

9

1

+

3

1

+1+...+2187

a

1

=

9

1

=3

−2

r=3a

n

=2187

Find n:

a

n

=a

1

⋅r

n−1

2187=3

−2

(3)

n−1

2187=3

n−3

3

7

=3

n−3

7=n−3

10=n

\begin{lgathered}\underline{\text{Find the sum:}}\\S_n=\dfrac{a_1(1-r^n)}{1-r}\\\\\\S_{10}=\dfrac{\frac{1}{9}(1-3^{10})}{1-3}\\\\\\.\quad =\dfrac{1-59,049}{(9)(-2)}\\\\\\.\quad =\dfrac{-59,048}{9(-2)}\\\\\\.\quad =\large\boxed{\dfrac{29,524}{9}}\end{lgathered}

Find the sum:

S

n

=

1−r

a

1

(1−r

n

)

S

10

=

1−3

9

1

(1−3

10

)

.=

(9)(−2)

1−59,049

.=

9(−2)

−59,048

.=

9

29,524

24 Answer: \bold{\dfrac{364}{9}}

9

364

Explanation:

\begin{lgathered}a_1=27\qquad r=\dfrac{1}{3}\qquad n=6\\\\S_n=\dfrac{a_1(1-r^n)}{1-r}\\\\\\S_6=\dfrac{27(1-\frac{1}{3}^6)}{1-\frac{1}{3}}\\\\\\.\quad =\dfrac{27(\frac{728}{729})}{\frac{2}{3}}\\\\\\.\quad =\dfrac{27(728)}{729}\cdot \dfrac{3}{2}\\\\\\.\quad =\large\boxed{\dfrac{364}{9}}\end{lgathered}

a

1

=27r=

3

1

n=6

S

n

=

1−r

a

1

(1−r

n

)

S

6

=

1−

3

1

27(1−

3

1

6

)

.=

3

2

27(

729

728

)

.=

729

27(728)

2

3

.=

9

364

25 Answer: n=7

Explanation:

\begin{lgathered}\{-6,\ -12,\ -24,\ ...\ \}\\\\a_1=-6\qquad r=2\qquad S_n=-762\\\\S_n=\dfrac{a_1(1-r^n)}{1-r}\\\\\\-762=\dfrac{-6(1-2^n)}{1-2}\\\\\\-762=\dfrac{-6(1-2^n)}{-1}\\\\\\\dfrac{-762}{6}=1-2^n\\\\-127=1-2^n\\\\-128=-2^n\\\\128=2^n\\\\2^7=2^n\\\\\large\boxed{7=n}\end{lgathered}

{−6, −12, −24, ... }

a

1

=−6r=2S

n

=−762

S

n

=

1−r

a

1

(1−r

n

)

−762=

1−2

−6(1−2

n

)

−762=

−1

−6(1−2

n

)

6

−762

=1−2

n

−127=1−2

n

−128=−2

n

128=2

n

2

7

=2

n

7=n

User LetsSeo
by
4.6k points
0 votes

23 Answer:
\bold{(29,524)/(9)}

Explanation:


(1)/(9)+(1)/(3)+1+...+2187\\\\\\a_1=(1)/(9)=3^(-2)\qquad r=3\qquad a_n=2187\\\\\underline{\text{Find n:}}\\a_n=a_1\cdot r^(n-1)\\2187=3^(-2)(3)^(n-1)\\2187=3^(n-3)\\3^7=3^(n-3)\\7=n-3\\10=n


\underline{\text{Find the sum:}}\\S_n=(a_1(1-r^n))/(1-r)\\\\\\S_(10)=((1)/(9)(1-3^(10)))/(1-3)\\\\\\.\quad =(1-59,049)/((9)(-2))\\\\\\.\quad =(-59,048)/(9(-2))\\\\\\.\quad =\large\boxed{(29,524)/(9)}

24 Answer:
\bold{(364)/(9)}

Explanation:


a_1=27\qquad r=(1)/(3)\qquad n=6\\\\S_n=(a_1(1-r^n))/(1-r)\\\\\\S_6=(27(1-(1)/(3)^6))/(1-(1)/(3))\\\\\\.\quad =(27((728)/(729)))/((2)/(3))\\\\\\.\quad =(27(728))/(729)\cdot (3)/(2)\\\\\\.\quad =\large\boxed{(364)/(9)}

25 Answer: n=7

Explanation:


\{-6,\ -12,\ -24,\ ...\ \}\\\\a_1=-6\qquad r=2\qquad S_n=-762\\\\S_n=(a_1(1-r^n))/(1-r)\\\\\\-762=(-6(1-2^n))/(1-2)\\\\\\-762=(-6(1-2^n))/(-1)\\\\\\(-762)/(6)=1-2^n\\\\-127=1-2^n\\\\-128=-2^n\\\\128=2^n\\\\2^7=2^n\\\\\large\boxed{7=n}

User DomaNitro
by
4.8k points